Critical Geography from Within: Embodied Standpoints, Visibilisation and Reparative Praxis - Behzadi, Negar Elodie (ACME, 2026)
This paper reflects on what it means to do critical geography today by tracing its complex history and situating it within my own positionality as a feminist political geographer inspired by post/de/anti-colonial perspectives. While critical geography is often located in the radical movements of the 1960s-1970s in North America and Europe, these accounts overlook wider and earlier histories of critique, and the contributions of non-white, non-male, and non-Anglophone thinkers. I argue that critical geography has always been plural, shaped by feminist, anti-racist, postcolonial, and Global South perspectives that have since become central to the discipline. Writing from a standpoint shaped by my own history of migration, displacement, and simultaneous privilege within academia, I emphasise that our positions influence the forms of critique we produce. I describe this approach as the production of knowledge from within out: a way of engaging with the world that acknowledges how embodied, emotional, and experiential ways of knowing can generate critical insight. From this perspective, I outline my two key commitments in doing critical geography today based on my own work. The first is a Politics of Visibilisation – making visible the systemic, intimate, and embodied violences of extraction, displacement, and exhaustion. The second is a Reparative Praxis, which asks how we might move beyond critique toward responsibility, creativity, and care. Drawing on feminist and art-based methodologies, I suggest that critical geography can be a reparative and participatory practice, one that not only exposes injustice but also nurtures resilience, connection, and the possibility of repair.